Effect of particle size on the dielectric properties of sodium potassium niobate -Portland cement composites - R. Potong (2018)
In this research, the effect of sodium potassium niobate, (Na0.5K0.5)NbO3(NKN) particle size on the dielectric properties of 0-3 non lead based piezoelectric cement based composites were investigated. NKN of various particle sizes (75, 225 and 450μ) were used at 50% by volume to produce the composites. Dielectric properties at various frequencies (0.1-20 kHz) were investigated. The results showed that the dielectric values of NKN-PC composites increased with increasing NKN particle size whereε at 1 kHz are 158.60 and 191.21 for composites with 75μ and 450μ NKN particle size respectively. The dielectric loss (tan) was found to reduce with increasing NKN particle size and the tanδ value was lowest at 0.39 for composite with 450μ NKN particle size.